Law, Debt, and Merchant Power : The Civil Courts of Eighteenth-Century Halifax - Muir, James, 1971- (Book collections on Project MUSE., 2016)
In the early history of Halifax (1749-1766), debt litigation was extremely common. In Law, Debt, and Merchant Power, James Muir offers an extensive analysis of the civil cases of the time as well as the reasons behind their frequency.